Racial Prejudice Through the Lens of Institutional Racism in Therese Anne Fowler's Novel A Good Neighborhood (2020) - Sibarani, Indra Prayuda; Al-Hafizh, Muhd (English Language and Literature, 2024)
This research analyses the novel A Good Neighborhood (2020) by Therese Anne Fowler. It explores the various causes, forms and impacts of racial prejudice experienced by the characters who are African-American. This research uses Critical Race Theory (CRT) especially Institutional Racism as the theoretical framework, and employs a descriptive qualitative method, with data derived from specific words, phrases, and sentences in the novel. The findings reveal that racial prejudice that is done by society and Institutions like Law Enforcement which includes Police Department, Judicial System and Correctional System, then Healthcare Department, and Media News Outlet manifests through generalisations and stereotypes, leading to verbal antagonism, avoidance, discrimination, and physical attack. The impacts of such prejudice include discrimination and oppression. The study underscores the pervasive and detrimental effects of racial prejudice on individuals and communities, highlighting the importance of addressing and eliminating such prejudices to achieve social justice and equity.